Comparison of job Satisfaction and job Stress on Mental health factors among female school Teachers: Impacts of Job Satisfaction and Job Stress on Mental Health Factors in Female School Teachers (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The aim of the present research was to find out the effects of job satisfaction and stress job onmental health factors among female teachers working in different types of schools of U.P. For thatpurpose, one hundred and sixty female teachers (N = 160) were selected as a sample from government andmissionary schools of U.P. An equal number of female teachers, i.e., (n = 80), were selected throughrandom sampling method from two types of school, viz., government and missionary. Job satisfactionscale of Dr. (Mrs.) Meera Dixit, and Indore teachers Job stressors scale of Dr. (Mrs.) Meena BuddhisagarRathod and Dr. Madhulika Verma were used as instruments for the study. Initially, the reliability statisticsof both the instruments was calculated to know the significance of the scales. According to the findingsof the study, it was found that female teachers of government school were significantly better in overallJob satisfaction, Intrinsic aspect of the job, Salary, Promotional Avenues, Service Conditions, PhysicalFacilities, Institutional Plan and Policies and Satisfaction with authorities than the over type of schoolteachers. It was further revealed that female teachers of missionary school significantly suffer fromoverall Job Stress, Overloadness, Role Conflict, Role Ambiguity and Frail Interpersonal Relationship. Asthere are different job satisfaction and stress conditions among school female teachers, it is thereforenecessary for every school to make their employees motivated and satisfied towards high performanceby adopting different techniques and methods.